The vacuum UV photoabsorption spectroscopy of the trans-dichloroethylene (1, 2-ClHC=CClH) in the 5–20 eV range: Experiment and theory. (August 2020) - Locht, R.; Dehareng, D.; Leyh, B.
Highlights: Vacuum UV photoabsorption spectrum of trans-1, 2-C2 H2 Cl2 for the first time between 5.0 eV and 20.0 eV. Analysis of electronic and vibrational Rydberg transitions. Detailed analysis for the first time of the valence transitions. Interpretation and assignments based on quantum chemical calculations. Abstract: This paper investigates in detail the vacuum UV photoabsorption spectrum of trans-1, 2-C2 H2 Cl2 in the 5–20 eV range using synchrotron radiation. Quantum chemical calculations are applied to the electronic transitions. Particular attention has been paid to the 2au (π)→2bg (π*) transition included in the broad band observed at 6.30 eV. The Rydberg 2au (π)→R3s transition is presumably observed at 6.27 eV. Below 6.0 eV the structure(s) are assigned to π→σ* transition(s). The abundantly structured spectrum observed between 7.0 eV and 12.0 eV has been analyzed in terms of vibronic transitions to ns- ( δ ¯ =0.844) and nd/4f- ( δ ¯ =0.03/0.011) Rydberg states, converging to the 2au −1 ionization continuum, to two series of np- ( δ ¯ = 0.66 and 0.40) states converging to the 5ag −1 continuum, to ns- ( δ ¯ =0.983) and nd- ( δ ¯ = –0.06) states converging to the 4bu −1 continuum and to two np-type ( δ ¯ = 0.51 and 0.26) series converging to the 1bg −1 continuum. These data are complemented by an analysis of the vibrational structure of the individual Rydberg states. Comparisons with previously reported values are provided. Several other spectral features Table S2 (see Supplementary Material) in the 12–20 eV range are tentatively assigned to transitions to Rydberg states converging to higher ionic excited states of trans-1, 2-C2 H2 Cl2 . Assignments of the vibrational structure of some of these transitions are also proposed.